2013
DOI: 10.1177/0022219413478663
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resources of Adults With Developmental Dyslexia

Abstract: The aim of our study was to describe specific psychological resources of adults with developmental dyslexia and compare them with psychological resources of adults without developmental dyslexia. Potential differences were analyzed in visual-spatial, creative, and motivational abilities. No evidence was found for either creative, or visuospatial superiority in adults with developmental dyslexia. The results suggest, however, that visual-spatial processing of nonverbal material by adults with developmental dysl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 52 publications
(71 reference statements)
4
18
0
1
Order By: Relevance
“…Similar results to the findings here, indicating the absence of difference between the groups in relation to creativity, were also found in a study undertaken by Lockiewicz et al (2013) and Tafti et al (2009), in which they compared the creative performance of subjects with dyslexia with that of subjects without learning difficulties -and did not ascertain differences between the groups. Some hypotheses have been raised to explain why discrepant results have not been found between the groups; these in general involve historical variables which underlie both creativity and dyslexia.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar results to the findings here, indicating the absence of difference between the groups in relation to creativity, were also found in a study undertaken by Lockiewicz et al (2013) and Tafti et al (2009), in which they compared the creative performance of subjects with dyslexia with that of subjects without learning difficulties -and did not ascertain differences between the groups. Some hypotheses have been raised to explain why discrepant results have not been found between the groups; these in general involve historical variables which underlie both creativity and dyslexia.…”
Section: Discussionsupporting
confidence: 88%
“…In the same way, Torrance and Safter (1999) emphasize that the emotional aspects have been considered to be elements of great importance in creativity, often even more important than cognitive factors. Such assertions could explain the results obtained in the present study and, in addition, would support investigations relating to emotional factors in dyslexia, which indicate a greater emotional sensitivity in this case (Lockiewicz et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A similar trend was observed with fifth‐ and sixth‐grade Greek students diagnosed with dyslexia, where participants reported using a surface approach more often, characterized by task‐avoidant behaviours (Polychroni et al, ). However, no differences were found between Polish adults with and without dyslexia on self‐reported task avoidance measurements (Lockiewicz, Bogdanowicz, & Bogdanowicz, ). These different findings could possibly be explained by various age‐related factors, particularly because those studies, which demonstrated differences in task‐focused and task‐avoidant behaviours, were focused on childhood.…”
Section: Introductionmentioning
confidence: 90%